Effectiveness of an Intervention to Enhance First Aid Knowledge among Early Childhood Education Students: A Pilot Study - Patxi León-Guereño; Laura Cid-Aldama; Héctor Galindo-Domínguez; Alaitz Amezua-Urrutia (MDPI AG, 2023)
Empowering early childhood education students from the beginning with the necessary knowledge and skills to act swiftly in emergency situations could be crucial in saving lives in certain cases. In order to improve the first aid knowledge and skills of early childhood education students, a pre/post study was conducted with a two-week intermediate intervention involving 13 early childhood education students. Their knowledge and skills in first aid were assessed using an ad-hoc instrument before and after the intervention. The results demonstrate a statistically significant improvement in all items related to first aid general knowledge, first aid kits, and CPR maneuvers, as well as in the overall scale. These findings provide evidence that early childhood education students can be equipped through low-cost interventions to acquire and apply certain essential first aid skills, such as dialing emergency services, understanding the purpose of first aid kit items, and recognizing vital signs in individuals, that may be crucial in saving lives in the future.